Longing for Ummah: From New Order Muslim to Reformasi Muslim in Indonesian Islamic novel, 1998-2004 - Ratmanee, Bancha (Connexion: Journal of Humanities and Social Sciences, 2023)
This research article aims to study the emotive of post-New Order Indonesian Muslims through the Indonesian Islamic novel Perempuan Berkalung Sorban and Ayat-Ayat Cinta published during 1998-2004. It deploys William Reddy’s historical method and emotive framework to explore the historical dynamics of Indonesian Muslim sentiments. The study found that Indonesian Islamic novels reveal a new emotive and a new Indonesian Muslim Ummah based on Islamic moral and gender equality, unlike the New Order era where the power and role of men over women.